Formulation and evaluation of controlled porosity osmotic pump tablets of verapamil hydrochloride - Nhat Hoang Thi Anh; Hung Pham Van; Xuan Dam Thanh; Quang Le Dinh; Duyen Nguyen Thi Thanh (Vietnam Journal of Science, Technology and Engineering, 2025)
Verapamil hydrochloride, a calcium channel blocker with pH-dependent solubility, was selected as the model drug for the development of osmotic pump tablets. The objective of this study was to prepare controlled porosity osmotic pump tablets containing 120 mg of verapamil hydrochloride that conform to the U.S. Pharmacopeia 2023 dissolution test requirements. The core tablets were formulated through wet granulation, utilising sodium chloride as an osmotic agent and succinic acid and citric acid as microenvironmental pH modifiers. The tablets were coated with a semi- permeable membrane containing Opadry CA and pore-forming agents such as PEG 400 (1.5:1), sorbitol, or PVP K30 in various ratios and weight gains. Dissolution tests revealed that drug release increased with the addition of pH modifiers. Sodium chloride served dual functions: enhancing core osmotic pressure to promote dissolution while also potentially reducing drug solubility, thereby diminishing dissolution. As for the membrane, increasing the amount of pore-forming agents and reducing the weight gain led to an increased drug release rate. The M7 tablets, containing 60 mg of NaCl, 60 mg of succinic acid, and 10 mg of citric acid in the core, and with membranes formulated with PEG 400 (1.5:1) at a 57.5% polymer ratio and 5% weight gain, successfully met the dissolution requirements of the U.S. Pharmacopeia 2023.